2011
DOI: 10.1186/cc10498
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: Canadian National Advisory Committee on Blood and Blood Products - Massive Transfusion Consensus Conference 2011: report of the panel

Abstract: In June 2011 the Canadian National Advisory Committee on Blood and Blood Products sponsored an international consensus conference on transfusion and trauma. A panel of 10 experts and two external advisors reviewed the current medical literature and information presented at the conference by invited international speakers and attendees. The Consensus Panel addressed six specific questions on the topic of blood transfusion in trauma. The questions focused on: ratio-based blood resuscitation in trauma patients; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 77 publications
0
82
0
3
Order By: Relevance
“…The treatment of major haemorrhage with the use of formulaic shock packs is a recent trend based on retrospective studies of military casualties, which suggested that mortality was lowest in those given a 1:1:1 ratio of packed red cells, FFP and platelets [8,9]. A Consensus Panel of the Canadian National Advisory Committee on Blood and Blood Products examined the evidence for this approach in 2011 [10]. It concluded that the survivorship bias has probably contributed substantially to the observed reduction in mortality seen in retrospective studies, and that there was a lack of evidence to support 1:1:1 blood component ratios as a standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of major haemorrhage with the use of formulaic shock packs is a recent trend based on retrospective studies of military casualties, which suggested that mortality was lowest in those given a 1:1:1 ratio of packed red cells, FFP and platelets [8,9]. A Consensus Panel of the Canadian National Advisory Committee on Blood and Blood Products examined the evidence for this approach in 2011 [10]. It concluded that the survivorship bias has probably contributed substantially to the observed reduction in mortality seen in retrospective studies, and that there was a lack of evidence to support 1:1:1 blood component ratios as a standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…25 Further, the Canadian National Advisory Committee on Blood and Blood Products has published a consensus developed at the Massive Transfusion Consensus Conference (June 2011, Toronto, Canada) that survivorship bias comprises a major obstacle in the proper interpretation of retrospective associations between transfusion ratios and trauma outcome, and limited scientific evidence currently exists to support ratio-driven (e.g., 1:1:1 ratios of RBC, plasma, and platelet units) transfusion protocols. 26 The effect of survivorship bias was shown compellingly by Snyder et al who confirmed a survival benefit with highratio transfusion in their cohort of 134 patients, but only when the ratio was characterized at 24 hr post-admission. 27 Conversely, when the transfusion ratio was analyzed as a time-dependent covariate, the survival benefit was not shown.…”
Section: Management Of Massive Transfusion In the Trauma Settingmentioning
confidence: 93%
“…Broadly speaking, rapid assessment of hemostasis may include standard hemostasis assays like prothrombin time (PT), PTT, fibrinogen, and platelet count or it may rely on viscoelastic whole-blood hemostasis assays [2]. Rapid hemostasis testing may be carried out in the clinical laboratory [3,4], in a satellite laboratory [5], or as point-of-care testing in the operating room or trauma suite [6][7][8][9][10][11].…”
Section: Clinical Situationmentioning
confidence: 99%